TOP2A expression predicts responsiveness to carfilzomib in myeloma and informs novel combinatorial strategies for enhanced proteasome inhibitor cell killing. Issue 2 (28th January 2021) - Reale, Antonia; Khong, Tiffany; Mithraprabhu, Sridurga; Savvidou, Ioanna; Hocking, Jay; Bergin, Krystal; Ramachandran, Malarmathy; Chen, Maoshan; Dammacco, Francesco; Ria, Roberto; Silvestris, Francesco; Vacca, Angelo; et al.
Abstract: Microarray was utilized to determine if a genetic signature associated with resistance to carfilzomib (CFZ) could be identified. Twelve human myeloma (MM) cell lines (HMCLs) were treated with CFZ and a cell-viability profile was assessed categorizing HMCLs as sensitive or resistant to CFZ. The gene expression profiles (GEP) of untreated resistant versus sensitive HMCLs revealed 29 differentially expressed genes. TOP2A, an enzyme involved in cell cycle and proliferation, was overexpressed in carfilzomib-resistant HMCLs. TOP2A protein expression levels, evaluated utilizing trephine biopsy specimens acquired prior to treatment with proteasome inhibitors, were higher in patients failing to achieve a response when compared to responding patients. Logistic-regression analysis confirmed that TOP2A protein expression was a highly significant predictor of response to PIs (AUC 0.738). Further, the combination of CFZ with TOP2A inhibitors, demonstrated synergistic cytotoxic effects in vitro, providing a rationale for combining topoisomerase inhibitors with CFZ to overcome resistance in MM.